OPTIMASI PENGGUNAAN EXCAVATOR DAN DUMP TRUCK PADA PROYEK X DENGAN METODE LINEAR PROGRAMMING - Imanda, Krisna; Sutandi, Arianti (Prodi Sarjana Teknik Sipil, FT, Universitas Tarumanagara, 2024)
The growth of construction projects in Indonesia demands efficient utilization of heavy equipment in infrastructure projects. One of the significant cost factors involves the use of heavy machinery such as Excavators and Dump Trucks. This study employs linear programming to optimize the usage of Excavators and Dump Trucks in a soil excavation project in Bogor. By minimizing the operational costs of heavy machinery, the research identifies the optimal number of equipment required to achieve the targeted volume of soil. The results indicate that employing the LP model with LINGO software significantly reduces project costs, saving approximately Rp368,445,800 per week compared to field costs. This research contributes to enhancing operational efficiency and reducing costs in construction projects through the optimization of heavy equipment utilization. The optimization of heavy equipment utilization in construction projects not only improves cost efficiency but also ensures the timely completion of projects within budget constraints. By leveraging mathematical models such as linear programming, this study demonstrates a practical approach to achieving these goals. The findings underscore the importance of strategic planning and efficient resource allocation in enhancing overall project performance and competitiveness in the construction industry. Abstrak Pertumbuhan industri konstruksi di Indonesia menuntut penggunaan alat berat yang efisien dalam proyek-proyek infrastruktur. Salah satu faktor biaya terbesar adalah penggunaan alat berat seperti excavator dan dump truck. Penelitian ini menggunakan pendekatan linear programming untuk mengoptimalkan penggunaan excavator dan dump truck dalam proyek penggalian tanah di Bogor. Dengan meminimalkan biaya operasional alat berat, studi ini berhasil mengidentifikasi penggunaan optimal alat berat yang diperlukan untuk mencapai volume tanah yang ditargetkan. Hasilnya menunjukkan bahwa penggunaan model linear programming dengan bantuan program LINGO dapat mengurangi biaya proyek secara signifikan, sekitar Rp368.445.800 per minggu, dibandingkan dengan biaya lapangan. Penelitian ini memberikan kontribusi dalam meningkatkan efisiensi operasional dan mengurangi biaya pada proyek konstruksi melalui optimasi penggunaan alat berat.